The Role of the Community in the Development of Creative Economy Tourism in the city of Baubau is based on the local wisdom of the Buton Palace - Trisetyasi*, Evi; Armiyani, Armiyani; Rafikas, Rafikas (Universitas Syiah Kuala, 2023)
Creative economy tourism is an essential sector in the economic development of Baubau City. In developing this sector, the role of the community is significant. Communities can be active in decision-making and implementing creative economy tourism development programs. The philosophy of life of the Bhutanese people, known as PO-5 (read; polymer), is an acronym for several philosophies, namely Popia-piara, Poangka-Angkataka, Pomae-Maeaka, Poma-masiaka, and Pobinci- Bincikikuli. The research uses the Participatory Action Research (PAR) method to analyze the role of the community in developing creative economic tourism in Baubau City. Through this approach, communities and researchers work together to define problems, identify possible solutions, and implement actions to improve local communities' economic and social well-being. The research results show that the weaving community is essential in developing creative economic tourism in Baubau City. They can contribute through innovative product development, marketing and tourism promotion, increasing community involvement in decision-making and empowering the local economy while remaining based on local wisdom. However, challenges are also faced in involving communities in developing creative economic tourism, including a lack of knowledge and skills and the need for access to resources and capital.